2016
DOI: 10.1002/adem.201600166
|View full text |Cite
|
Sign up to set email alerts
|

A Review of SiC Fiber Oxidation with a New Study of Hi‐Nicalon SiC Fiber Oxidation

Abstract: The linear and parabolic oxidation rate constants and activation energies for SiC fibers available in the literature are reviewed for the first time. Oxidation experiments are also conducted with Hi-Nicalon SiC fibers over 700-1 300 C in dry O 2 with thermogravimetric analysis. Linear oxidation kinetics are observed from 700 to 800 C and parabolic kinetics are observed from 900 to 1 300 C. The linear and parabolic oxidation rate constant activation energies are determined to be 83 and 108 kJ mol À1 , respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 50 publications
(136 reference statements)
1
32
0
Order By: Relevance
“…The Hi-Nicalon™ fiber oxidation observed in the study by Wilson and Opila was governed by linear kinetics at temperatures below 900˚C that then transitioned to parabolic kinetics at higher temperatures, as shown in Figure 4 30 . The temperature dependence of the oxidation rate constants in Wilson and Opila's study 30 were found to be in good agreement with the rate constants reported by others on the oxidation of CVD-SiC in dry O2 17,21 . …”
Section: Boron Nitride Oxidation Kineticssupporting
confidence: 89%
See 4 more Smart Citations
“…The Hi-Nicalon™ fiber oxidation observed in the study by Wilson and Opila was governed by linear kinetics at temperatures below 900˚C that then transitioned to parabolic kinetics at higher temperatures, as shown in Figure 4 30 . The temperature dependence of the oxidation rate constants in Wilson and Opila's study 30 were found to be in good agreement with the rate constants reported by others on the oxidation of CVD-SiC in dry O2 17,21 . …”
Section: Boron Nitride Oxidation Kineticssupporting
confidence: 89%
“…Sylramic fibers exhibited linear TGA weight change at ≤1000˚C exposures, from which oxide growth at these exposures was assumed to be governed by linear oxidation kinetics based on TGA results. The linear rate constants, kl, were calculated from these measured oxide thicknesses per unit time, 30 reported as µm/ h in Table 5. Parabolic oxide growth was assumed from parabolic TGA weight change at ≥ 1100˚C.…”
Section: Oxidation Resultsmentioning
confidence: 99%
See 3 more Smart Citations